Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1155/2013/676425
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenesis May Involve the Prooxidant and Proinflammatory Effects of Ferryl Hemoglobin

Abstract: Oxidized cell-free hemoglobin (Hb), including covalently cross-linked Hb multimers, is present in advanced atherosclerotic lesions. Oxidation of Hb produces methemoglobin (Fe3+) and ferryl hemoglobin (Fe4+ = O2−). Ferryl iron is unstable and can return to the Fe3+ state by reacting with specific amino acids of the globin chains. In these reactions globin radicals are produced followed by termination reactions yielding covalently cross-linked Hb multimers. Despite the evanescent nature of the ferryl state, here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 54 publications
(81 reference statements)
4
52
0
1
Order By: Relevance
“…While other studies have reported associations between circulating CFH and alterations in endothelial function in models of atherosclerosis, malaria, and sickle cell disease (38)(39)(40), there have been few prior studies of the direct effects of CFH on microvascular endothelial permeability (41). Oxidized CFH, which is present in atherosclerotic plaques, results in intercellular gap formation and increased permeability in cultured endothelial cell monolayers (42,43). Hypoxia-responsive genes including HIF have also been implicated in hemoprotein-induced endothelial permeability in dermal microvascular endothelial cells (41).…”
Section: Discussionmentioning
confidence: 99%
“…While other studies have reported associations between circulating CFH and alterations in endothelial function in models of atherosclerosis, malaria, and sickle cell disease (38)(39)(40), there have been few prior studies of the direct effects of CFH on microvascular endothelial permeability (41). Oxidized CFH, which is present in atherosclerotic plaques, results in intercellular gap formation and increased permeability in cultured endothelial cell monolayers (42,43). Hypoxia-responsive genes including HIF have also been implicated in hemoprotein-induced endothelial permeability in dermal microvascular endothelial cells (41).…”
Section: Discussionmentioning
confidence: 99%
“…ferrylHb undergoes intermolecular cross-linking of its globin chains forming aggregates, which induces the expression of adhesion molecules in vascular endothelial cells that support the recruitment of macrophages into the vessel wall (Silva et al, 2009; Potor et al, 2013). Similarly to heme, ferrylHb activates endothelial cells through NFκB activation (Silva et al, 2009).…”
Section: Possible Roles Of Heme-induced Innate Immune Receptor Activamentioning
confidence: 99%
“…Leírtuk azt is, hogy a sejtek a reaktív oxigéngyökökkel szemben egy indukálható, endogén védelmi mechanizmussal rendelkeznek, ez a transzkripciós szinten regulálható hemoxigenáz-1 enzim (HO-1) és a poszttranszkripciós szinten szabályozott ferritinrendszer [25,26,27,28,29]. A rendszer bilirubin mediálta antioxidáns potenciálján túl befolyással bír a sejtek, szövetek differenciálódására a ferritinnek a vasanyagcserére gyakorolt hatása által, sőt a korábban melléktermékként számon tartott szén-monoxidnak is van szabályzó funkciója, antitrombotikus, antiapoptotikus és antiinfl ammatiós sajátosságú [30,31].…”
Section: A Rop Kezeléseunclassified